2014
DOI: 10.1186/1824-7288-40-62
|View full text |Cite
|
Sign up to set email alerts
|

Progress in pediatrics in 2013: choices in allergology, endocrinology, gastroenterology, hypertension, infectious diseases, neonatology, neurology, nutrition and respiratory tract illnesses

Abstract: This review will provide new information related to pathophysiology and management of specific diseases that have been addressed by selected articles published in the Italian Journal of Pediatrics in 2013, focusing on allergology, endocrinology, gastroenterology, hypertension, infectious diseases, neonatology, neurology, nutrition and respiratory tract illnesses in children. Recommendations for interpretation of skin prick test to foods in atopic eczema, management of allergic conjunctivitis, hypertension and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…10 On the other hand, intestinal probiotics affect the amount of bilirubin in the enterohepatic circulation by reducing the degradation of bound bilirubin. 11 Meanwhile, they are able to stimulate intestinal peristalsis, which also benefits the elimination of bilirubin. It has previously been reported that oral administration of probiotics showed markedly better effects than those of routine blue light phototherapy.…”
Section: Discussionmentioning
confidence: 99%
“…10 On the other hand, intestinal probiotics affect the amount of bilirubin in the enterohepatic circulation by reducing the degradation of bound bilirubin. 11 Meanwhile, they are able to stimulate intestinal peristalsis, which also benefits the elimination of bilirubin. It has previously been reported that oral administration of probiotics showed markedly better effects than those of routine blue light phototherapy.…”
Section: Discussionmentioning
confidence: 99%